Pengembangan Sistem Informasi Penyediaan Prajurit Tni Au Berbasis Web Untuk Meningkatkan Efisiensi dan Transparansi Proses Rekrutmen - Permadi Yoga Mitra Perdana; Alcianno G. Gani; Muryan Awaludin (Jurnal Mahasiswa Informatika dan Desain, 2025)
The recruitment process for Indonesian Air Force personnel is crucial for ensuring the smooth operation and continuity of national defense functions. However, challenges in this process include low efficiency and lack of transparency. This research aims to develop a web-based information system to enhance the efficiency and transparency of the Indonesian Air Force personnel recruitment process. The system is designed to integrate various stages of recruitment, from registration and administrative selection to the announcement of results. The methodology includes needs analysis, system design, implementation, and evaluation. The study results indicate that the developed information system successfully reduces data processing time, facilitates information access for prospective personnel, and improves the accuracy and reliability of recruitment data. Therefore, this system is expected to effectively enhance the quality and transparency of the Indonesian Air Force personnel recruitment process